Sul pensiero pedagogico di Riccardo Massa - Franco Cambi (Firenze University Press, 2021)
Riccardo Massa has been an interpreter of the Italian Theoretical Pedagogy: this article identifies four main focuses of his thought: the important research on the pedagogical epistemology, the reflection on young people, the "clinic of education" and the challenge of the school in the postmodern era.